2011
DOI: 10.1038/ki.2011.41
|View full text |Cite
|
Sign up to set email alerts
|

Urinary neutrophil gelatinase-associated lipocalin distinguishes pre-renal from intrinsic renal failure and predicts outcomes

Abstract: In established acute kidney injury (AKI), serum creatinine poorly differentiates prerenal and intrinsic AKI. A damage-associated nephron biomarker, neutrophil gelatinase-associated lipocalin (NGAL) could be a better discriminator. We tested the hypothesis that urinary NGAL distinguishes intrinsic and prerenal AKI, and tested its performance in the prediction of a composite outcome that included progression to a higher RIFLE (“risk, injury, failure, loss of function, end stage renal disease”) severity class, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
138
3
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(161 citation statements)
references
References 30 publications
11
138
3
4
Order By: Relevance
“…This unexpected finding highlights the contribution of the development of intrinsic AKI during the hospitalization to the overall incidence and importance of potentially modifiable risk factors, such as nephrotoxic medications. Indeed, structural urinary biomarkers such as neutrophil gelatinase-associated lipocalin (NGAL), that are typically upregulated in intrinsic AKI but not in functional prerenal azotemia, are also dramatically elevated in children with NS (21,22). These findings further support the notion that observed AKI is not merely due to intravascular volume depletion.…”
Section: Discussionsupporting
confidence: 74%
“…This unexpected finding highlights the contribution of the development of intrinsic AKI during the hospitalization to the overall incidence and importance of potentially modifiable risk factors, such as nephrotoxic medications. Indeed, structural urinary biomarkers such as neutrophil gelatinase-associated lipocalin (NGAL), that are typically upregulated in intrinsic AKI but not in functional prerenal azotemia, are also dramatically elevated in children with NS (21,22). These findings further support the notion that observed AKI is not merely due to intravascular volume depletion.…”
Section: Discussionsupporting
confidence: 74%
“…These biomarkers displayed a progressive increase across the spectrum of AKI (no AKI , prerenal , intrinsic). Although the definition of prerenal AKI used is not universally accepted, this investigation of a mixed medical-surgical ICU population corroborates a previous single-center study that showed that biomarkers may help distinguish between prerenal and intrarenal causes of AKI (43). Our hope is that, in the near future, investigations move away from nonstandardized and potentially confusing terms such as prerenal and view kidney injury in terms of biomarkers of functional and structural damage.…”
Section: Biomarkers In the Setting Of Critical Illness And Sepsissupporting
confidence: 61%
“…After adjusting for clinical covariates known to impact critical illness and AKI, UCysC levels were independently associated with sepsis (OR=3. 43 (32). Note, in this study, that there was no interaction between sepsis and AKI and that these findings are in line with smaller studies that investigated the ability of UCysC to detect early AKI and predict the need for RRT and death in a mixed surgical and medical ICU population (34,35).…”
Section: Biomarkers In the Setting Of Critical Illness And Sepsismentioning
confidence: 99%
“…63 GVHD may therefore contribute to kidney injury fundamentally by two mechanisms: directly through cytokine-and immune-related injury, including glomerular deposits triggering nephrotic syndrome, and tubulitis; or indirectly through nephrotoxicity induced by calcineurin inhibitors used as prophylaxis against GVHD. 17,18 Moreover, GVHD-associated nephrotoxicity may result from severe GVHD with diarrhea and subsequent dehydration, as well as from CMV reactivation because of GVHD treatment with high-dose prednisolone. 7,19 An augmented risk of the development of AKI in non-myeloablative HCT has been linked to CMV reactivation in itself.…”
Section: Pathogenesismentioning
confidence: 99%